Efficacy of GABA aminotransferase inactivator OV329 in models of neuropathic and inflammatory pain without tolerance or addiction - Jonah L. Wirt; Luana Assis Ferreira; Carlos Henrique Alves Jesus; Taylor J. Woodward; Idaira Oliva; Zhili Xu; Jonathon D. Crystal; Robert H. Pepin; Richard B. Silverman; Andrea G. Hohmann (Proceedings of the National Academy of Sciences, 2025)
Dysregulation of GABAergic inhibition is associated with pathological pain. Consequently, enhancement of GABAergic transmission represents a potential analgesic strategy. However, therapeutic potential of current GABA agonists and modulators is limited by unwanted side effects. We postulated that inhibition of GABA’s degradation enzyme, GABA aminotransferase (GABA-AT), would increase endogenous GABA levels and produce analgesia. We evaluated antinociceptive efficacy of the potent GABA-AT inhibitor OV329 in rodent models of neuropathic and inflammatory pain and assessed possible side effects (i.e., reward and motor impairment). OV329 attenuated the development and maintenance of mechanical and cold hypersensitivities induced by the chemotherapeutic agent paclitaxel. Prophylactic OV329, administered systemically, normalized paclitaxel-induced increases in glutamate levels and suppressed neuropathic nociception. Intrathecal OV329 suppressed paclitaxel-induced mechanical hypersensitivity, elevating GABA, and reducing glutamate levels in the lumbar spinal cord, consistent with a spinal site of action. Furthermore, OV329 largely synergized with paclitaxel to enhance 4T1 tumor cell line cytotoxicity without altering viability of nontumor cells. OV329 also attenuated inflammation-induced mechanical hypersensitivity induced by intraplanar injection of complete Freund’s adjuvant (CFA) with efficacy comparable to morphine. Unlike morphine, OV329 did not produce reward in a conditioned place preference assay in mice and was not self-administered intravenously by rats. Antinociceptive efficacy of OV329 was observed at doses that did not impair motor function or produce tolerance following chronic dosing. Thus, inhibition of GABA-AT with OV329 represents a unique therapeutic strategy to alleviate neuropathic and inflammatory pain with no apparent abuse liability, potentially producing a beneficial spectrum of pharmacological effects through enzymatic regulation.